2018
DOI: 10.1101/503201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperinsulinemia promotes aberrant histone acetylation in triple negative breast cancer

Abstract: words) 28Excess levels of insulin relative to glucose in the blood, or hyperinsulinemia, is 29 considered to be a poor prognostic indicator for patients with triple negative breast 30 cancer (TNBC). While this association has been recognized for some time, the 31 mechanistic role of hyperinsulinemia in promoting TNBC remains unclear. We show that 32 insulin treatment leads to genome-wide increase in histone acetylation, in particular at 33 H3K9, through the PI3K/AKT/mTOR pathway in MDA-MB-231 cells. Genome-wid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For example, the elevated levels of leptin and resistin under obese conditions are reported to facilitate cell proliferation, metastasis, stemness, or alter intratumoral oxidative status and the components of immune system both in vitro and in vivo [8,49,50]. In addition, hyperinsulinemia or chronic insulin stimulation occurs in obese individuals is associated with tumor progression in TNBC by altering mitochondrial activity, histone modification, and several oncogenic signaling pathways [48,51,52]. Moreover, these adipocyte-secreted factors can also induce SERPINE1 level to cooperatively promote cancer progression [45,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the elevated levels of leptin and resistin under obese conditions are reported to facilitate cell proliferation, metastasis, stemness, or alter intratumoral oxidative status and the components of immune system both in vitro and in vivo [8,49,50]. In addition, hyperinsulinemia or chronic insulin stimulation occurs in obese individuals is associated with tumor progression in TNBC by altering mitochondrial activity, histone modification, and several oncogenic signaling pathways [48,51,52]. Moreover, these adipocyte-secreted factors can also induce SERPINE1 level to cooperatively promote cancer progression [45,53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-established characteristics of SERPINE1 on cancer progression, in our study, we demonstrated that SERPINE1 is a crucial factor linking obesity to tumor radioresistance in several potential mechanisms. The dysregulated lipid metabolism has been shown to link with a higher level of acetyl-CoA pool and promotes histone acetylation both in vitro and in vivo [51,56]. Acetylation of certain genes further leads to promoting cancer stemness, metastatic capacity, and therapeutic resistance [57].…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic KRAS signaling in murine pancreatic acinar cells also promotes elevated histone acetylation in an AKT- and ACLY-dependent manner, even prior to tumor formation, and genetic deletion of Acly suppresses pancreatic carcinogenesis ( Carrer et al 2019 ). Insulin signaling, which activates the PI3K-AKT pathway, can also drive an increase in histone acetylation in cancer cells ( Carrer et al 2019 , Senapati et al 2019 ). In addition to oncogenic signaling, DNA damage signaling also promotes ACLY-S473 phosphorylation within the nucleus in an ATM- and AKT-dependent manner.…”
Section: Metabolic Rewiring In Cancer Impacts the Tumor Epigenomementioning
confidence: 99%
“…Histone acetylation modification is an important apparent modification [6]. A large number of studies have shown that the decrease of acetylation caused by the overexpression of histone deacetylase or the decrease of acetylase expression in cancer cells is closely related to the occurrence of tumor [7,8,9,10,11]. There are reports that acetylation H4 the 16th lysine (H4K16ac) residue of histone can promote the transcription of corresponding genes by changing the spatial conformation of chromatin [12,13].…”
Section: Introductionmentioning
confidence: 99%